Media Bias In The Coverage Of The Third Debate Of The 2024 Presidential Candidates - Mutiah; Rindang Senja Andarini; Leti Karmila; Randy William (Journal Commedies, 2025)
This research aims to find out how the bias of online media Metrotvnews.com and SINDOnews.com in the coverage of the 2024 presidential debate for the period January 6-13. This research uses a qualitative approach with the Robert N. Entman model framing analysis method. The news analyzed were 52 news from Metrotvnews.com and 38 news from SINDOnews.com. The results showed that there were differences in news framing between the two media. Metrotvnews.com showed media framing by highlighting presidential candidate number 1, Anies Baswedan, through a narrative that featured the programs of presidential candidate number 1. Meanwhile, SINDOnews.com framed the news by showing support for candidate number 3, Ganjar Pranowo, through his attitude, appearance, understanding of the debate theme and experience. Both media show support for the presidential candidate through news coverage that emphasizes the advantages of the presidential candidate. So that the news that appears on Metrotvnews.com and SINDOnews.com is biased, this violates the principles of objectivity and media independence.